(untitled) (Fiep Bulletin - online, 2014)
The current conditions of life and, especially, the situation of the health imposes to the society a constant reflection. Enormous challenges have been found in the section of the degenerative chronic diseases. Even the wealther countries have been finding many difficulties to stop the progress of diseases as the obesity, that some decades ago affected a small portion of the population and today became epidemic. In this way, the city hall of Maringá in partnership with IES has developed the program Healthy Maringá and the Fair Maringá Health Space. This work presents the results of 678 people’s evaluations that involved the readiness for physical activities (PAR-Q), the questionnaire of risks factors (ACSM), the test of flexibility (sit-and-reach) and the test of the step to evaluate the aerobic condition. The results indicate that the nutritional transition is in advanced stage, more than fifty percent of the people are overweight. The presence of avoidable risk factors is also quite high and it requests immediate initiatives so avoid that these conditions become high cost diseases and deep impact in the individuals’ health and in the social balance.